Untargeted metabolomics and transcriptomics joint analysis of the effects of polystyrene nanoplastics on lipid metabolism in the mouse liver - Chen, Lijuan; Sui, Guoyuan; Wu, Jin; Li, Ning; Zhang, Zhe; Du, Ying; Lü, Meijun; Yan, Xiaorui; Pan, Guowei; Jia, Lianqun (Lipids in health and disease, 2025)
Micro/nanoplastics (MNPs), as emerging environmental pollutants, are widely present in environments that are essential for human survival. They exist in vast quantities and possess stable properties, making them challenging to manage. Some reports indicated that there is a positive correlation between the production of MNPs and the incidence of obesity. The liver serves as both the central hub for lipid metabolism and a prime target for MNPs toxicity. These studies revealed that MNPs can lead to increased hepatic lipid accumulation, suggesting that they may be potential obesogens. However, the specific metabolic changes and possible mechanisms involved remain to be elucidated. This study focuses on the impact of nanoplastics (NPs) on liver lipid metabolism, using C57BL/6J mice (hereinafter referred to as C57 mice) as the research subjects, and exposing them to 100 nm NPs at 1000 µg/L continuously for 12 weeks. The study revealed that (1) NPs led to nondietary weight gain together with an increase in fat volume and mass in mice. (2) NPs significantly increased serum total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) levels, with notable differences between groups. Notably, NPs exposure induced opposing effects on serum lipid profiles, elevating high-density lipoprotein cholesterol (HDL-C) concentrations while suppressing triglyceride (TG) levels, though intergroup differences failed to reach statistical significance. (3) NPs caused multiple inflammatory responses in the liver, with significant lipid deposition. (4) Untargeted metabolomics analysis indicated that NPs exposure led to significant alterations in various lipid metabolites, particularly glycerophospholipids. Additionally, transcriptomics reveals that differentially expressed genes (DEGs) triggered by NPs exposure are predominantly involved in metabolic routes including lipid metabolism and cytochrome P450 (CYP). Taken together, these findings suggested that alterations in lipid metabolism resulting from NPs exposure may involve arachidonic acid metabolism. Phosphatidylcholine (PC) could be the key substance, and the CYP gene family (Cyp2c23, Cyp2c40) might be the critical genes regulating liver lipid metabolism during NPs exposure. This study has demonstrated that NPs exposure induced obesity and hepatic lipid accumulation in male mice independently of food intake. The integrated omics data identified dysregulated PC metabolism and CYP gene family expression, suggesting their involvement in arachidonic acid-associated pathways. These findings provided preliminary mechanistic clues linking NP exposure to hepatic lipid metabolism dysregulation and helped to elucidate the adverse effects of NPs on liver lipid metabolism.